Severe fatigue is associated with diminished lung function and elevated Galectin-9 levels in early systemic sclerosis - van Eeden, Charmaine; Rezaeifar, Maryam; Elezzabi, Muhammad; Redmond, Desiree; Gniadecki, Robert; Abey, Andrew; Reynolds, Erin; Sholter, Dalton; Shahbaz, Shima; Elahi, Shokrollah; Khan, Lamia; Mason, Andrew; et al. (Frontiers in Immunology, 2025)
IntroductionSymptoms resembling myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) frequently affect patients with rheumatic diseases, but little is known about their frequency and disease manifestations, particularly in systemic sclerosis (SSc) patients. We sought to determine if severe fatigue in SSc patients with early disease (< 7 years) is associated with increased disability, inflammation and fibrosis.MethodsIn this exploratory cross-sectional study, 51 SSc patients were recruited locally (UofA cohort). Disability, disease damage accrual, inflammatory markers and, indicators of fibrotic and vascular complications (e.g. lung function, nailfold capillaroscopy) were compared between patients with and without severe fatigue. Fatigue was assessed using validated questionnaires (e.g. FACIT, MFI) and ME/CFS criteria. Findings were further corroborated in the national CSRG (Canadian Scleroderma Research Group) SSc cohort (n=126).ResultsSSc patients with severe fatigue had significantly increased disability, reduced lung function capacity, and elevated Galectin-9 levels when compared to patients without fatigue. Galectin-9 levels correlated with reduced pulmonary function, and increased disease damage accrual. Further analysis in the UofA cohort suggested that indictors associated with disease progression such as reduced nailfold capillary density, and elevated VEGF, LTα and IL-16 were present in severely fatigued patients.DiscussionSevere fatigue in SSc patients is associated with increased disability, reduced pulmonary function and increased vascular remodeling. We propose that ME/CFS-like symptoms in patients with SSc may be indicative of sub-clinical inflammation and fibrosis. Further studies are required to determine whether Gal-9,may be a useful tool for the stratification of SSc patients - particularly those with severe fatigue resembling ME/CFS.